Diversity and spatial distribution of pelagic amphipods in the Western Ross Sea and the Pacific sector of the Southern Ocean - Minutoli, Roberta; Guglielmo, Letterio; Bonanno, Angelo; Genovese, Simona; Ferreri, Rosalia; Di Paola, Davide; Grillo, Marco; Guglielmo, Ylenia; Swadling, Kerrie M.; Granata, Antonia; Aronica, Salvatore (Frontiers in Marine Science, 2025)
Amphipods play an important role in Southern Ocean trophic chains. Considering the key role of Pacific Ocean and sea ice ecosystems in the Earth system and the growing impact of global environmental change, it is important to collect information on the status of marine amphipod biodiversity. A total of 410 zooplankton samples were collected by BIONESS (Bedford Institute of Oceanography Net Environmental Sampling System) from 27 stations during the Vth ItaliaAntartide Expedition, between 25 November 1989 and 12 January 1990, in the Pacific sector of the Southern Ocean, from New Zealand to the Western Ross Sea. The aim of this study was to describe the composition, relative abundance, spatial distribution and latitudinal boundaries of pelagic amphipods. An additional goal was to describe the main water masses and the pack ice extent and its temporal evolution during the cruise and relate species assemblages to the physical structure of the region. A total of 2058 specimens of pelagic amphipods was counted, and 43 taxa belonging to 18 families were identified. Hyperiella dilatata was the most abundant species (45% of relative abundance) followed by Primno macropa (12%), Pseudorchomene plebs (12%) and Hyperiella macronyx (8%). The composition of amphipod species differed significantly between stations. Three different clusters were identified through the k-means algorithm based on species abundance and confirmed by an NMDS plot. Cluster 1 was mainly composed of the southernmost stations, Cluster 2 included the northernmost stations, while the stations in the central part were grouped in Cluster 3. A correlation between species composition and the sampled layers at the different stations was highlighted. Knowledge of amphipod biodiversity by means of this study can represent a baseline for future studies, to provide evidence of potential changes as signal of alterations in the environment.